108k views
4 votes
Find the simplified form of the expression. Given your answer in scientific notation (8 x 10^4)(9 x 10^8)

User Rob Murray
by
6.0k points

1 Answer

6 votes


(8 * {10}^(4) )(9 * {10}^(8) ) \\ = 8 * 9 * {10}^(4) * {10}^(8 ) \\ = 72 * {10}^(4 + 8) \\ = 7.2 * 10 * {10}^(12) \\ = 7.2 * {10}^(13)

This is the answer with step by step explanation

User Edouardbriere
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.